Toward a New History of Catholic Education - Lannie, Vincent P. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Some of the major extant works on the history of American Catholic education are discussed to provide a background for an outline of the general framework of the author's projected three-volume history. In this projected study, the author will: 1) examine the broad spectrum of educational agencies that have helped to shape the Catholic mind in an ever-changing American society; 2) examine a host of educational alternatives open to the church at different periods in her history, and place the development of the parochial school system in proper perspective; 3) examine new insights and interpretations in the various fields of American history and American religious history, look at the insights of the behavioral and social sciences, and attempt to incorporate empirical research data and techniques. Tentative titles and lines of investigation are spelled out for each of the three volumes. (Author/JLB)
ERIC Note: Paper presented at the Annual Meeting, American Educational Research Association, Chicago, Illinois, April 6, 1972.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Catholic Schools; Educational History; Parochial Schools; Speeches